Same-Sex Marriage as a Human Rights Freedom in Indonesia: The Perspective of Pancasila and the Marriage Law - Dedihasriadi, La ode; Hsieh, Ju-Lan; Umar, Wahyudi (Jambura Law Review, 2022)
Human rights are basic rights that are inherent in humans, so the state is obliged to protect, respect and defend them. Same-sex marriage is a human right. The purpose of this paper is to find out how the legal perspective in Indonesia regarding the legality of same-sex marriage on the basis of freedom of human rights. This research method is normative based with an analytical approach. The results of this study conclude that same-sex marriage on the basis of freedom of human rights does not have a philosophical legal standing because it is contrary to the values contained in Pancasila as the ground norm in Indonesia. On the other hand, Sociologically, same-sex marriage is not in accordance with the culture and culture of the Indonesian nation where its citizens are citizens who uphold the values of the Almighty God. Substantially, same-sex marriage legislation is also not contained in Law No.1 of 1974 concerning marriage which has been changed to Law No. 16 of 2019 concerning amendments to Law No. 1 of 1974 concerning marriage.